Pengaruh Senam Ergonomis terhadap Penurunan Kadar Asam Urat pada Lansia di Wilayah Kerja Puskesmas Peukan Bada Aceh Besar - Silva Madia Martin; Syukriadi Syukriadi; Ellyza Fazlylawati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Gout can be triggered by several interconnected factors, such as genetic predisposition, family history, obesity, hypertension, heart disease, age, being overweight, and insufficient fluid intake. Recommended exercises for gout sufferers include regular exercise, stretching, and gymnastics. Ergonomic exercise is important for lowering uric acid, especially among elderly people with hyperuricemia. Hyperuricemia is a condition where blood uric acid levels are elevated. This study aims to determine whether ergonomic exercise lowers uric acid levels in the elderly at the Peukan Bada Public Health Center. The study used a quasi-experimental design with a one-group pretest-posttest approach. The sample included all 17 elderly with gout, selected using the total sampling method. Uric acid was measured using a Uric Acid measuring device. Data were analyzed using the Paired t-test. The results showed a p-value of 0.000. This proves ergonomic exercise affects uric acid levels in the elderly at the Peukan Bada Public Health Center. In conclusion, ergonomic exercise influences uric acid levels in the elderly at the Peukan Bada Public Health Center. Patients should regularly perform ergonomic exercises, using correct movements and staying within their physical abilities. Ergonomic exercises can be done 3-4 times a week to improve metabolism, maintain joint flexibility, and reduce uric acid in the body.